Assessing Risk Management Implementation in Quality Management System - Fathurohman; Muhamad Ekhsan; Nur Laela (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of quality management system requires to consider risks and opportunities in planning the system, refers to clause 6.1 ISO 9001:2015. The management of PT. Dharma Poliplast implemented a risk mitigation system to fulfill the needs, expectations and Key Performance Indicators of stakeholders but quality problems still recur. This research aimed to analyze the implementation of risk management according to ISO 9001: 2015 and ISO 31000 requirements and by comparing the implementation of risk management to a best practice company. The approach used in this research was descriptive qualitative using secondary data from the internal company. The results of this research proved that PT. Dharma Poliplast has implemented risk management in accordance with requirements of ISO 9001:2015 and ISO 31000 and best practices effectively.